PENGARUH ATRIBUT DESTINASI TERHADAP KEPUASAN WISATAWAN ASING DI OBYEK WISATA CANDI BOROBUDUR - , SRI MUJIYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Borobudur temple is one of the worldâs heritage which attract for both International tourists and domestic tourists. Tourist who visit the temple is a user who give assesment to the temple. The quality of the atributes which provided become the key of assesment. Price is one of the attribute in this assesment. This research focus on any attributes which attached in Borobudur temple. Those are lanscape, culture and history, good service, accesibility, local people behaviour, safety and sanitation, weather condition and price. The aim of this reserach is knowing the relation among those attributes and how the foreign tourist give assesment to it. This research used quantitative and qualitative methodes. The finding of this reserach are landscape as the most significance attributes (53%), Culture and History (46,7%), local behaviour toward tourists (40%), accessibility (36,7%), safety and sanitation (36,7%), weather condition (16,7%) and price (6,7%). The tourists give their confirmation as their satisfaction.